A checklist of the water mites (Acari: Hydrachnidia) of Iran - Pesic, Vladimir; Saboori, Alireza (Zootaxa, 2007)
Using published records and original data from recent research, a checklist was compiled of the water mite (Acari: Hydrachnidia) fauna of Iran. The checklist contains 145 species, in 38 genera and 25 families of water mites. Seven of these species (4.8%) are Holarctic, 31 (21.4%) are Palaearctic, 23 (15.9%) are W-Palaearctic, 20 (13.8%) are SW-Palaearctic, and 15 (10.4%) are “Middle East” in their distribution. Moreover, 46 (31.7%) of these species are endemic to Iran. Seven species are new to Iranian fauna. Atractides baderi Schwoerbel & Sepasgozarian is replaced with Atractides balneatoris nov. nom.